Genetic predisposition and environmental danger signals initiate chronic autoimmune hepatitis driven by CD4+ T cells. Issue 2 (1st July 2013) - Hardtke‐Wolenski, Matthias; Fischer, Katja; Noyan, Fatih; Schlue, Jerome; Falk, Christine S.; Stahlhut, Maike; Woller, Norman; Kuehnel, Florian; Taubert, Richard; Manns, Michael P.; Jaeckel, Elmar
<x xml:space="preserve">Abstract</x> Autoimmune hepatitis (AIH) is defined as a chronic liver disease with loss of tolerance against liver tissue eventually leading to cirrhosis if left untreated. 80%‐90% of patients can be treated with a life‐long immunosuppression. Unfortunately, there are strong drug‐related side effects and steroid‐refractory patients. Therefore, there is a need for a model system to investigate the complex immunopathogenesis of this chronic disease and subsequently to develop new therapeutic interventions. We developed a new model of experimental murine AIH (emAIH) by a self‐limited adenoviral infection with the hepatic autoantigen formiminotransferase cyclodeaminase (FTCD). After an initial transient hepatitis there was a chronic evolving AIH, finally leading to portal and lobular fibrosis. We could show that the genetic predisposition provided by the NOD background was essential for creating a fertile field for the development of liver‐specific autoimmunity. However, a strong environmental trigger was additionally necessary to initiate the disease. Besides the break of humoral tolerance, T‐cell tolerance against hepatic self‐antigens was also broken and CD4+ T cells were identified as essential drivers of the disease. As the disease was successfully treated with prednisolone and budesonide, the model will be helpful to develop and test new therapeutic interventions. Conclusion: We developed a new murine AIH model closely resembling AIH in patients that explains the mechanisms of AIH pathophysiology. In addition, emAIH provides options to test therapeutic alternatives for patients not achieving remission, with reduced side effects of chronic nonspecific immunosuppression. (Hepatology 2013;58:718–728)